Analysis of Promotion Strategies through the Addition of Play Areas with Cats at Mostcat Cafe Batam - Sweiney Sweiney; Natal Olotua Sipayung; Wahyudi Ilham; Rezki Alhamdi (CV. Publikasi Indonesia, 2024)
Mostcat Cafe is the first cafe in Batam that integrates the concept of direct interaction with cats. Adopting the